Acts of Gaiety LGBT Performance and the Politics of Pleasure - Warner, Sara (University of Michigan Press, 2012)
Acts of Gaiety explores the mirthful modes of political performance by LGBT artists, activists, and collectives that have inspired and sustained deadly serious struggles for revolutionary change. The book explores antics such as camp, kitsch, drag, guerrilla theater, zap actions, rallies, manifestos, pageants, and parades alongside more familiar forms of "legitimate theater." Against queer theory's long-suffering romance with mourning and melancholia and a national agenda that urges homosexuals to renounce pleasure if they want to be taken seriously by mainstream society, Acts of Gaiety seeks to reanimate notions of "gaiety" as a political value for LGBT activism.